Ibn ‘Arabi and The Ambiguous Verses of the Quran: Beyond The Letter and Pure Reason - Arif, Syamsuddin (IAIN Surakarta, 2019)
This article attempts to clarify this issue and explain Ibn ‘Arabi’s interpretive method, particularly in dealing with the so-called ‘ambiguous verses’ (ayat mutashabihat)of the Holy Quran, on the basis of meticulous reading of several relevant chapters of his kitab al-Futuhat al-Makkiyyah(‘Meccan Illuminations’) and other treatises. The discussion reveals Ibn ‘Arabi’s approach to Quranic interpretation which rests on the assumption that all the possible meanings that the Arabic language allows for any given word or group of words in the Quran are valid, and that rejection of any one of these meanings would imply limiting God’s knowledge and inappropriately saying that God was unaware of the various ways in which His Word could be interpreted. In contrast to the theologians (Mutakallimun)and philosophers (Falasifah), Ibn ‘Arabi rejects rational interpretation (ta’wil ‘aqli)outright. If reason finds the ambiguous verses of the Quran unacceptable, this only proves its own imperfection and failure to comprehend, not the necessity of interpretation. While he insists that one’s reading of the Quran must conform to the Arabic language as spoken by its original recipient, Ibn ‘Arabi more often than not offers surprising and highly original interpretations that seek to unveil the mystical treasures hidden in the text.